The Kinesin-Related Protein MCAK Is a Microtubule Depolymerase that Forms an ATP-Hydrolyzing Complex at Microtubule Ends - Hunter, Andrew W. (Mol Cell, 2003)
MCAK belongs to the Kin I subfamily of kinesin-related proteins, a unique group of motor proteins that are not motile but instead destabilize microtubules. We show that MCAK is an ATPase that catalytically depolymerizes microtubules by accelerating, 100-fold, the rate of dissociation of tubulin from microtubule ends. MCAK has one high-affinity binding site per protofilament end, which, when occupied, has both the depolymerase and ATPase activities. MCAK targets protofilament ends very rapidly (on-rate 54 µM(−1)·s(−1)), perhaps by diffusion along the microtubule lattice, and, once there, removes ~20 tubulin dimers at a rate of 1 s(−1). We propose that up to 14 MCAK dimers assemble at the end of a microtubule to form an ATP-hydrolyzing complex that processively depolymerizes the microtubule.